Utility of thromboelastography and/or thromboelastometry in adults with sepsis: a systematic review - Müller, Marcella C; Meijers, Joost CM; Vroom, Margreeth B; Juffermans, Nicole P (Critical care (London, England), 2014)
Introduction Coagulation abnormalities are frequent in sepsis. Conventional coagulation assays, however, have several limitations. A surge of interest exists in the use of point-of-care tests to diagnose hypo- and hypercoagulability in sepsis. We performed a systematic review of available literature to establish the value of rotational thromboelastography (TEG) and thromboelastometry (ROTEM) compared with standard coagulation tests to detect hyper- or hypocoagulability in sepsis patients. Furthermore, we assessed the value of TEG/ROTEM to identify sepsis patients likely to benefit from therapies that interfere with the coagulation system. Methods MEDLINE, EMBASE, and the Cochrane Library were searched from 1 January 1980 to 31 December 2012. The search was limited to adults, and language was limited to English. Reference lists of retrieved articles were hand-searched for additional studies. Ongoing trials were searched on http://www.controlled-trials.com and http://www.clinicaltrials.gov . Studies addressing TEG/ROTEM measurements in adult patients with sepsis admitted to the ICU were considered eligible. Results Of 680 screened articles, 18 studies were included, of which two were randomized controlled trials, and 16 were observational cohort studies. In patients with sepsis, results show both hyper- and hypocoagulability, as well as TEG/ROTEM values that fell within reference values. Both hyper- and hypocoagulability were to some extent associated with diffuse intravascular coagulation. Compared with conventional coagulation tests, TEG/ROTEM can detect impaired fibrinolysis, which can possibly help to discriminate between sepsis and systemic inflammatory response syndrome (SIRS). A hypocoagulable profile is associated with increased mortality. The value of TEG/ROTEM to identify patients with sepsis who could possibly benefit from therapies interfering with the coagulation system could not be assessed, because studies addressing this topic were limited. Conclusion TEG/ROTEM could be a promising tool in diagnosing alterations in coagulation in sepsis. Further research on the value of TEG/ROTEM in these patients is warranted. Given that coagulopathy is a dynamic process, sequential measurements are needed to understand the coagulation patterns in sepsis, as can be detected by TEG/ROTEM.